(untitled) - Rogers, Bruce (Thành phố Hồ Chí Minh, 2000)
There's no substitute for practice in learning a language, and the more practice the better. That's why this terrific guidebook/CD package is exactly what ESL students need to develop their English-language and test-taking skills. Designed to supplement TOEFL Success or to be used by itself book.
Keywords: English language,English language; Examinations,Study and teaching